Collection development in UK university libraries. Issue 1 (3rd January 2017) - Hunt, Stuart
Abstract : Purpose: The purpose of this paper is to highlight collection development activity in UK higher education libraries and to place it within both a conceptual and strategic context. Design/methodology/approach: This paper uses a theoretical approach to collection development and content strategy derived from literary theory to contextualise debates. It uses current examples from collection management within UK academic libraries. Findings: This paper suggests that collection development is not exclusively a library practitioner activity but needs to be considered within a wider context that takes account of multiple strands of collection selection and management. Collection development cannot be considered in isolation but alongside collection management and in relation to content strategy. Research limitations/implications: This paper includes consideration of the topic of collection development that is influenced by other disciplines, notably literary theory. This suggests that research in library science should include input from other disciplines. Practical implications: This paper includes implications for content development within academic libraries that suggest that a re-focus at the strategic level of content is required. Originality/value: This paper introduces a conceptual register to collection development outside of traditional library science models and posits a move to strategy.